(untitled) (Geography and Tourism, 2024)
The study aimed to evaluate the interest in spiritourism in Mexico among Polish tourists and to showcase the country's potential for developing tequila and mezcal-related tourism. To achieve this objective, the authors conducted a survey that obtained 209 responses. The survey was carried out in Polish using the CAPI technique, and the questionnaire was distributed via Facebook travel groups and Instagram, reaching an audience potentially interested in traveling to Mexico. The survey took place from May to October 2024. The article examines the historical background of alcohol in the region, the production processes of various spirits, and Mexico’s attractions related to alcoholic beverages to highlight the country's potential for the development of spiritourism. The results indicate that Polish tourists' interest in Mexican cuisine varies, with the highest engagement among those who have visited Mexico. While many recognize popular dishes like tacos and guacamole, travelers to Mexico display deeper knowledge of traditional foods and a stronger interest in tequila and mezcal distilleries.